Peningkatan Pengetahuan Masyarakat Tentang Cuci Tangan Terkait Pandemi Covid-19 di Wilayah Kerja Puskesmas Kuranji Padang - Yuanita Ananda; Nelwati Nelwati; Zifriyanthi Minanda Putri; Muthmainnah Muthmainnah; Edo Gusdiansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
Entering the new normal era, people have started to carry out economic and social activities as usual. Even now the community is not afraid to be in a crowd without wearing a mask and not following the health protocol that has been socialized by the government. It is known that the number of new cases of patients infected with Covid-19 every day is increasing with the most cases being in the city of Padang. One area that experienced an increase in the Covid case rate in the city of Padang was in the working area of the Kuranji Padang Health Center, in the Korong Gadang Village. The increase in these cases is due to lack of knowledge and awareness of the community against Covid-19 transmission and also the limitations of health workers in providing education to the community also become obstacles in the midst of this pandemic. Therefore, it is highly necessary to provide more in-depth education to people in the working area of the Kuranji Padang Health Center. Education was done online by giving a google form link to the public so that the pre-test and post-test scores are known and a booklet is given and this activity was carried out on July 7-8, 2020. The evaluation results showed that there is an increase in public knowledge about washing hands based on post-test. The activity would be monitored by the Health Center for the continuous education.